Anion-doped high-voltage electric performance lead-free piezoelectric ceramics, preparation and application thereof
Patent Information
- Application Number
- CN202611478739.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-27
Smart Images

Figure CN122977844A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of piezoelectric ceramics technology, and in particular to anion-doped lead-free piezoelectric ceramics with high piezoelectric properties, their preparation and application. Background Technology
[0002] Piezoelectric ceramics are a class of functional materials capable of converting mechanical energy into electrical energy, and are widely used in electronic components such as transducers, sensors, and actuators. Since the advent of lead zirconate titanate (PZT) ceramics, lead-based piezoelectric ceramics have long dominated the market due to their excellent piezoelectric properties and good temperature stability. However, lead-based ceramics contain more than 60% lead, posing serious hazards to the environment and human health during production, use, and disposal. Therefore, developing high-performance lead-free piezoelectric ceramics has become an important research direction in the field of piezoelectric materials.
[0003] Among numerous lead-free piezoelectric ceramic systems, potassium sodium niobate (KNN)-based ceramics are considered one of the most promising PZT alternatives due to their high piezoelectric response, high Curie temperature, and environmentally friendly properties. Studies have shown that through cation doping (such as Li...) + Sb 5+ Ta 5+ (etc.) can effectively regulate the phase structure of KNN-based ceramics, construct room-temperature multiphase coexistence, significantly improve piezoelectric performance, and the piezoelectric constant of some systems has surpassed that of commercial PZT-5H ceramics.
[0004] However, existing research mainly focuses on the impact of cation doping on the properties of KNN-based ceramics, but this approach still faces several insurmountable technical bottlenecks: First, the core mechanism by which cation doping (such as Li, Ta, Sb, etc.) improves the piezoelectric constant of KNN-based ceramics is the induction of polymorphic phase boundaries (PPBs) near room temperature. However, these phase boundaries are highly sensitive to temperature, and temperature fluctuations can easily cause the material to deviate from the optimal phase boundary composition, leading to a sharp deterioration in piezoelectric performance. This inherent contradiction of "high piezoelectricity accompanied by differential thermal stability" has become a key challenge restricting the practical application of cation-doped KNN-based ceramics. Second, cation doping can only be regulated within limited dimensions such as the ionic radius and valence state at the A or B sites, and the selection of dopant elements is limited by physicochemical constraints such as ionic radius matching and solid solubility, resulting in an increasingly saturated tunable space. While complex multi-element co-doping can further improve performance, the composition design becomes increasingly complex, and the performance improvement gradually slows down. Finally, there is still significant controversy regarding the microscopic mechanisms of important doping elements such as Li and Sb in existing research. For example, the origin of the tetragonal phase induced by Li doping and the actual substitution valence state of Sb remain to be clarified, which limits the rational design capability of cation doping strategies.
[0005] Therefore, there is an urgent need for a new method that breaks through the traditional cation doping paradigm, which can simultaneously achieve high voltage response and good temperature stability of KNN-based lead-free piezoelectric ceramics without relying on the polymorphic phase boundary temperature-sensitive mechanism. Summary of the Invention
[0006] The purpose of this invention is to provide anion-doped lead-free piezoelectric ceramics with high piezoelectric properties, their preparation and application. By replacing Ag2O with AgF, fluoride ions replace oxygen ions, i.e., anion doping, the piezoelectric properties of the prepared lead-free piezoelectric ceramics are significantly improved.
[0007] To achieve the above objectives, this invention provides anion-doped lead-free piezoelectric ceramics with high voltage performance. The general chemical formula of the lead-free piezoelectric ceramics is: 0.945K. 0.50 Na 0.50 Nb 0.95 A 0.05 O3-0.04Bi 0.5 (B) 0.5 ZrO3-0.015AgSbO 3-x F 2x Where A is Sb, and B includes at least one of Na, K, Li, and Ag; 0 < x ≤0.4, x This represents the molar percentage of AgF replacing Ag2O.
[0008] This invention also provides a method for preparing the above-mentioned anion-doped lead-free piezoelectric ceramic with high voltage performance, comprising the following steps: S1. According to the molar ratio of the general chemical formula, sodium carbonate, potassium carbonate, niobium pentoxide, antimony trioxide, bismuth trioxide, zirconium dioxide, silver oxide and silver fluoride are used as raw materials. After being ball-milled separately, they are dried and mixed evenly to obtain raw material powder. S2. The raw material powder obtained in S1 is pre-calcined at 700~950℃ for 4~8h. After the heat preservation is completed, it is cooled to room temperature, rolled ball milled again, and dried to obtain the calcined powder. S3. The calcined powder obtained in S2 is granulated, pressed and debinded in sequence to obtain a ceramic body. S4. Sinter the ceramic green body obtained in S3 at 1050~1120℃ for 2~8h to obtain a piezoelectric ceramic body; S5. Silver electrodes are deposited on the surface of the piezoelectric ceramic body obtained in S4, and then it is placed in silicone oil for electric field polarization to obtain lead-free piezoelectric ceramic.
[0009] Preferably, in S1 and S2, the dispersion medium for the rolling ball mill is anhydrous ethanol, and the rolling ball milling time is 4-12 hours.
[0010] Preferably, in S3, granulation is performed by adding a polyvinyl alcohol solution to the calcined powder for granulation, wherein the concentration of the polyvinyl alcohol solution is 6-10 wt%.
[0011] Preferably, in step S3, the pressing is performed by using an electric tablet press to compress the granulated powder into tablets, with the pressure of the electric tablet press being 8-12 MPa.
[0012] Preferably, in S3, the temperature for discharging the adhesive is 750-850℃, and the discharging time is 80-100min.
[0013] Preferably, in S5, the temperature of the silicone oil is 25-35℃, the electric field strength for electric field polarization is 2~4kV / mm, and the electric field polarization time is 20~40min.
[0014] This invention also provides the application of the above-mentioned anion-doped lead-free piezoelectric ceramics with high voltage properties in the preparation of high-sensitivity sensors.
[0015] Therefore, the present invention, employing the above-mentioned anion-doped lead-free piezoelectric ceramic with high voltage performance, its preparation, and its application, has the following beneficial effects: (1) This invention utilizes fluoride ions (F... - ) Replace oxygen ions (O 2- The anion doping method of F utilizes F - With O 2- Similar ionic radii, lower charge numbers, and stronger electronegativity introduce defect structures into the crystal lattice and enhance local structural distortion, resulting in a significant sharpening of the dielectric peak. This leads to a stronger polarization response at the phase boundary, manifested as sharpening of the dielectric peak and a significant increase in the piezoelectric constant.
[0016] (2) This invention achieves uniform doping of fluoride ions, with a simple and controllable process that is easy to implement for industrial production. This anion doping strategy complements the cation doping strategy, opening up a new technical path for the performance optimization of KNN-based lead-free piezoelectric ceramics, and has significant scientific and application value.
[0017] (3) The piezoelectric ceramic material described in this invention does not contain lead, is an environmentally friendly material, and has a wide range of applications.
[0018] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0019] Figure 1 These are the XRD patterns of the lead-free piezoelectric ceramics of Examples 1-4 and Comparative Example 1 of the present invention; Figure 2 This is a schematic diagram showing the change of relative permittivity of the lead-free piezoelectric ceramic of Comparative Example 1 of the present invention with temperature. Figure 3 This is a schematic diagram showing the change of relative permittivity of the lead-free piezoelectric ceramic of Embodiment 1 of the present invention with temperature; Figure 4 This is a schematic diagram showing the change of relative permittivity of the lead-free piezoelectric ceramic as a function of temperature in Embodiment 2 of the present invention; Figure 5 This is a schematic diagram showing the change of relative permittivity of the lead-free piezoelectric ceramic of Embodiment 3 of the present invention with temperature; Figure 6 This is a schematic diagram showing the change of relative permittivity of the lead-free piezoelectric ceramic as a function of temperature in Embodiment 4 of the present invention. Detailed Implementation
[0020] The present invention will be further described below with reference to the accompanying drawings and embodiments. Unless otherwise defined, the technical or scientific terms used in this invention should be understood in their ordinary sense by those skilled in the art. The features mentioned above or in the specific examples mentioned in this invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the invention and are not intended to limit the scope of the invention.
[0021] This invention provides anion-doped lead-free piezoelectric ceramics with high voltage performance. The general chemical formula of the lead-free piezoelectric ceramics is: 0.945K. 0.50 Na 0.50 Nb 0.95 A 0.05 O3-0.04Bi 0.5 (B) 0.5 ZrO3-0.015AgSbO 3-x F 2x Where A is Sb, and B includes at least one of Na, K, Li, and Ag; 0 < x ≤0.4, x This represents the molar percentage of AgF replacing Ag2O.
[0022] It should be noted that the "-" in the general formula represents a homogeneous compound formed by multi-component doping.
[0023] This invention introduces A-site elements (Sb, Ta, etc.) and zirconate Bi into potassium sodium niobate ceramics. 0.5 (B) 0.5 ZrO3 and AgSbO3 were cationicly modified and sintered to obtain a piezoelectric ceramic structure with multiphase coexistence at room temperature. This multiphase coexistence structure can refine ferroelectric domains, reduce polarization barriers, and thus optimize piezoelectric performance. This invention further uses AgF instead of the traditional raw material Ag2O to achieve fluoride ion (F... - ) for oxygen ions (O 2-The substitution of fluoride ions at lattice sites, i.e., anion doping, is a process where fluoride ions, compared to oxygen ions, carry less and stronger electronegativity. Their substitution introduces positively charged defects into the lattice, while simultaneously strengthening the chemical bond between fluoride ions and coordinating cations, inducing stronger local lattice distortion. This distortion then affects the phase structure, sharpening the dielectric peak and resulting in a stronger polarization response at the phase boundary, manifested as a sharpening of the dielectric peak and a significant increase in the piezoelectric constant.
[0024] The lead-free piezoelectric ceramic material prepared by this invention has a relative permittivity of 2594~4098 and a piezoelectric constant of 480~618 pC / N, achieving an improvement in the piezoelectric performance of KNN-based lead-free piezoelectric ceramics. Furthermore, this piezoelectric ceramic material does not contain lead, making it an environmentally friendly material.
[0025] The molar percentage of each component in the lead-free piezoelectric ceramic of this invention needs to be strictly controlled; wherein, the main phase component "0.945K" 0.50 Na 0.50 Nb 0.95 A 0.05 The atomic ratios of K, Na, Nb, A, and O in "O3" should be 0.50, 0.50, 0.95, 0.05, and 3, respectively, based on valence balance; the component "Bi" 0.5 (B) 0.5 In "ZrO3", the atomic ratios of Bi, (B), Zr, and O must be 0.5, 0.5, 1, and 3, respectively; in "AgSbO3", the atomic ratios of Ag, Sb, and O must be 1, 1, and 3, respectively. When these ratios are deviated from, the phase structure of the ceramic will change significantly, and the domain structure will change accordingly, leading to a decrease in piezoelectric performance. If the ratios deviate significantly, excess elements are likely to form impurity phases during the doping process, which remain in the multiphase piezoelectric ceramic structure, further deteriorating the piezoelectric performance.
[0026] Preferably, in the general chemical formula x The value range is 0.1≤ x ≤0.4.
[0027] In this invention, the fluorine ion doping amount x When ∠=0, meaning no fluorine ion doping has been introduced, the piezoelectric properties of lead-free piezoelectric ceramics are relatively low; as ∠=0, the piezoelectric properties of lead-free piezoelectric ceramics are relatively low; x As the concentration increases, the amount of fluoride ions increases, significantly improving dielectric and piezoelectric properties; however, when... x When the fluoride ion content exceeds 0.4, excessive fluoride ions can easily lead to excessive lattice distortion, which in turn reduces dielectric and piezoelectric properties.
[0028] This invention also provides a method for preparing the above-mentioned anion-doped lead-free piezoelectric ceramic with high voltage performance, comprising the following steps: S1. According to the molar ratio of the general chemical formula, sodium carbonate, potassium carbonate, niobium pentoxide, antimony trioxide, bismuth trioxide, zirconium dioxide, silver oxide and silver fluoride are used as raw materials. After being ball-milled separately, they are dried and mixed evenly to obtain raw material powder. S2. The raw material powder obtained in S1 is pre-calcined at 700~950℃ for 4~8h. After the heat preservation is completed, it is cooled to room temperature, rolled ball milled again, and dried to obtain the calcined powder. S3. The calcined powder obtained in S2 is granulated, pressed and debinded in sequence to obtain a ceramic body. S4. Sinter the ceramic green body obtained in S3 at 1050~1120℃ for 2~8h to obtain a piezoelectric ceramic body; S5. Silver electrodes are deposited on the surface of the piezoelectric ceramic body obtained in S4, and then it is placed in silicone oil for electric field polarization to obtain lead-free piezoelectric ceramic.
[0029] Preferably, in S1 and S2, the dispersion medium for the rolling ball mill is anhydrous ethanol, and the rolling ball milling time is 4-12 hours.
[0030] Even more preferably, the rolling ball mill uses a nylon grinding jar and zirconium balls.
[0031] In a further preferred embodiment, in S2, pre-firing involves placing the raw material powder into an alumina crucible for pre-firing.
[0032] Preferably, in step S3, granulation involves adding a polyvinyl alcohol solution to the calcined powder for granulation, wherein the concentration of the polyvinyl alcohol solution is 6-10 wt%. By controlling the concentration and amount of the polyvinyl alcohol solution within the above range, this invention can improve powder flowability and green body mechanical strength, and helps obtain a green body with a more uniform density. If the concentration of the polyvinyl alcohol solution is below 6 wt%, the sample is prone to becoming misshapen, making it impossible to obtain lead-free piezoelectric ceramic material. If the concentration of the polyvinyl alcohol solution is above 10 wt%, the piezoelectric performance is easily reduced or the sample contains pores, resulting in the inability to obtain a dense lead-free piezoelectric ceramic material.
[0033] In some specific embodiments of the present invention, the concentration of the polyvinyl alcohol solution is 10 wt%.
[0034] Preferably, in step S3, the pressing is performed by using an electric tablet press to compress the granulated powder into tablets, with the pressure of the electric tablet press being 8-12 MPa.
[0035] More preferably, the sheet shape obtained by pressing includes one of the following: round, square, and oval; during pressing, the granulated powder is placed in a mold with a cavity.
[0036] Preferably, in S3, the temperature for discharging the adhesive is 750-850℃, and the discharging time is 80-100min.
[0037] Preferably, in S5, the temperature of the silicone oil is 25-35℃, the electric field strength for electric field polarization is 2~4kV / mm, and the electric field polarization time is 20~40min.
[0038] This invention also provides the application of the above-mentioned anion-doped lead-free piezoelectric ceramics with high voltage properties in the preparation of high-sensitivity sensors.
[0039] Example 1 This invention provides anion-doped lead-free piezoelectric ceramics with high voltage performance, the chemical formula of which is: 0.945K. 0.50 Na 0.50 Nb 0.95 Sb 0.05 O3-0.04Bi 0.5 (Na) 0.5 ZrO3-0.015AgSbO 2.9 F 0.2 ,in, x It is 0.1.
[0040] The preparation method of the above-mentioned anion-doped lead-free piezoelectric ceramic with high voltage performance includes the following steps: S1. According to the molar ratio of the general chemical formula, sodium carbonate, potassium carbonate, niobium pentoxide, antimony trioxide, bismuth trioxide, zirconium dioxide, silver oxide and silver fluoride are used as raw materials. The weighed raw materials are added to a nylon ball mill jar, and then anhydrous ethanol and zirconium balls are added as dispersion media. The mixture is ball-milled for 8 hours, dried and mixed evenly to obtain raw material powder.
[0041] S2. Place the raw material powder obtained in S1 into a corundum crucible, pre-calcine at 850℃ for 6 hours, cool to room temperature after the heat preservation is completed, and then roll ball mill again (the parameters of the rolling ball mill are the same as those in S1). After drying, the calcined powder is obtained.
[0042] S3. Add an 8wt% polyvinyl alcohol aqueous solution to the calcined powder obtained in S2 to granulate it; place the granulated powder in a mold with a diameter of 10mm, and use an electric tablet press to press it into a small round disc with a diameter of 10mm and a thickness of 1mm under a pressure of 10MPa. Then, remove the binder at 800℃ for 90min to obtain a ceramic green body.
[0043] S4. The ceramic blank obtained in S3 is sintered at 1085℃ for 4 hours to obtain a piezoelectric ceramic body.
[0044] S5. Silver electrodes are deposited on the surface of the piezoelectric ceramic body obtained in S4, and then placed in silicone oil at 30℃. Under an electric field strength of 3kV / mm, the ceramic body is polarized for 30 minutes to obtain lead-free piezoelectric ceramic.
[0045] Example 2 This invention provides anion-doped lead-free piezoelectric ceramics with high voltage performance, the chemical formula of which is: 0.945K. 0.50 Na 0.50 Nb 0.95 Sb 0.05 O3-0.04Bi 0.5 (Na) 0.5 ZrO3-0.015AgSbO 2.8 F 0.4 ,in x The value is 0.2. The preparation method of the above-mentioned anion-doped lead-free piezoelectric ceramic with high voltage performance is the same as that in Example 1.
[0046] Example 3 This invention provides anion-doped lead-free piezoelectric ceramics with high voltage performance, the chemical formula of which is: 0.945K. 0.50 Na 0.50 Nb 0.95 Sb 0.05 O3-0.04Bi 0.5 (Na) 0.5 ZrO3-0.015AgSbO 2.7 F 0.6 ,in x The value is 0.3. The preparation method of the above-mentioned anion-doped lead-free piezoelectric ceramic with high voltage performance is the same as that in Example 1.
[0047] Example 4 This invention provides anion-doped lead-free piezoelectric ceramics with high voltage performance, the chemical formula of which is: 0.945K. 0.50 Na 0.50 Nb 0.95 Sb 0.05 O3-0.04Bi 0.5 (Na) 0.5 ZrO3-0.015AgSbO 2.6 F 0.8 ,in x The value is 0.4. The preparation method of the above-mentioned anion-doped lead-free piezoelectric ceramic with high voltage performance is the same as that in Example 1.
[0048] Example 5 This invention provides anion-doped lead-free piezoelectric ceramics with high voltage performance, the chemical formula of which is: 0.945K. 0.50 Na 0.50 Nb 0.95 Sb 0.05 O3-0.04Bi 0.5 (Na) 0.5 ZrO3-0.015AgSbO 2.9 F 0.2,in, x It is 0.1.
[0049] The preparation method of the above-mentioned anion-doped lead-free piezoelectric ceramic with high voltage performance includes the following steps: S1. According to the molar ratio of the general chemical formula, sodium carbonate, potassium carbonate, niobium pentoxide, antimony trioxide, bismuth trioxide, zirconium dioxide, silver oxide and silver fluoride are used as raw materials. The weighed raw materials are added to a nylon ball mill jar, and then anhydrous ethanol and zirconium balls are added as dispersion media. The mixture is ball-milled for 4 hours, dried and mixed evenly to obtain raw material powder.
[0050] S2. Place the raw material powder obtained in S1 into a corundum crucible, pre-calcine at 700℃ for 8 hours, cool to room temperature after the heat preservation is completed, and then roll ball mill again (the parameters of the rolling ball mill are the same as those in S1). After drying, the calcined powder is obtained.
[0051] S3. Add a 6wt% polyvinyl alcohol aqueous solution to the calcined powder obtained in S2 to granulate it; place the granulated powder in a mold with a diameter of 10mm, and use an electric tablet press to press it into a small round disc with a diameter of 10mm and a thickness of 1mm under a pressure of 8MPa. Then, remove the binder at 750℃ for 80min to obtain a ceramic green body.
[0052] S4. The ceramic blank obtained in S3 is sintered at 1050℃ for 8 hours to obtain a piezoelectric ceramic body.
[0053] S5. Silver electrodes are deposited on the surface of the piezoelectric ceramic obtained in S4, and then placed in silicone oil at 25℃. Under an electric field strength of 2kV / mm, the ceramic is polarized for 40 minutes to obtain lead-free piezoelectric ceramic.
[0054] Example 6 This invention provides anion-doped lead-free piezoelectric ceramics with high voltage performance, the chemical formula of which is: 0.945K. 0.50 Na 0.50 Nb 0.95 Sb 0.05 O3-0.04Bi 0.5 (Na) 0.5 ZrO3-0.015AgSbO 2.9 F 0.2 ,in, x It is 0.1.
[0055] The preparation method of the above-mentioned anion-doped lead-free piezoelectric ceramic with high voltage performance includes the following steps: S1. According to the molar ratio of the general chemical formula, sodium carbonate, potassium carbonate, niobium pentoxide, antimony trioxide, bismuth trioxide, zirconium dioxide, silver oxide and silver fluoride are used as raw materials. The weighed raw materials are added to a nylon ball mill jar, and then anhydrous ethanol and zirconium balls are added as dispersion media. The mixture is ball-milled for 12 hours, dried and mixed evenly to obtain raw material powder.
[0056] S2. Place the raw material powder obtained in S1 into a corundum crucible, pre-calcine at 950℃ for 4 hours, cool to room temperature after the heat preservation is completed, and then roll ball mill again (the parameters of the rolling ball mill are the same as those in S1). After drying, the calcined powder is obtained.
[0057] S3. Add a 10wt% polyvinyl alcohol aqueous solution to the calcined powder obtained in S2 to granulate it; place the granulated powder in a mold with a diameter of 10mm, and use an electric tablet press to press it into a small round disc with a diameter of 10mm and a thickness of 1mm under a pressure of 12MPa. Then, remove the binder at 850℃ for 100min to obtain a ceramic green body.
[0058] S4. The ceramic blank obtained in S3 is sintered at 1120℃ for 2 hours to obtain a piezoelectric ceramic body.
[0059] S5. Silver electrodes are deposited on the surface of the piezoelectric ceramic body obtained in S4, and then placed in silicone oil at 35℃. Under an electric field strength of 4kV / mm, the ceramic body is electrically polarized for 20 minutes to obtain lead-free piezoelectric ceramic.
[0060] Comparative Example 1 The difference from Example 1 is that, x The K value is 0. The chemical formula for lead-free piezoelectric ceramics is: 0.945K. 0.50 Na 0.50 Nb 0.95 Sb 0.05 O3-0.04Bi 0.5 (Na) 0.5 ZrO3-0.015AgSbO3. Everything else is the same as in Example 1.
[0061] The lead-free piezoelectric ceramics prepared in Examples 1-4 and Comparative Example 1 were characterized by X-ray diffraction, and the results are as follows: Figure 1 As shown, Examples 1-4 and Comparative Example 1 all have 7 characteristic peaks between 20-70°, which are
[100] ,
[110] ,
[002] ,
[200] ,
[210] ,
[211] , and
[220] as the angle increases, indicating that the lead-free piezoelectric ceramic of the present invention is a perovskite ceramic. A split peak appears near 45-46°, namely the
[002] and
[200] peaks, with their peak intensity ratio deviating from 1:2 or 2:1, excluding pure T or O phases, indicating that the lead-free piezoelectric ceramic has a multiphase coexistence structure; in the lead-free piezoelectric ceramic...x Content ≤ 0 x The peak shapes of the XRD patterns within the range of ≤0.4 remain basically consistent, indicating that the lead-free piezoelectric ceramic structure of the present invention is relatively stable and always exhibits multiphase coexistence.
[0062] The lead-free piezoelectric ceramics prepared in Examples 1-4 and Comparative Example 1 were left to stand in air for 24 hours and then used as samples for electrical performance testing according to IEEE standards. The results are shown in Table 1.
[0063] Table 1. Electrical properties and Curie temperature of Examples 1-4 and Comparative Example 1
[0064] Note: d 33 It is the piezoelectric constant; ε r tan is the relative permittivity; δ Dielectric loss; T c The Curie temperature.
[0065] Table 1 shows that the relative permittivity of the lead-free piezoelectric ceramics in Examples 1-4, where AgF replaces Ag₂O, is 2594~4098. Appropriate fluorine doping can improve the relative permittivity of the piezoelectric ceramic material. The piezoelectric constant of the lead-free piezoelectric ceramics in Examples 1-4, where AgF replaces Ag₂O, is 480~618 pC / N. x When the doping concentration is 0.3, the piezoelectric constant reaches its maximum value of 618 pC / N, and the relative permittivity reaches its maximum value of 4098, indicating that the introduction of fluoride ions is most significant at this doping concentration; when x At a concentration of 0.4, the performance decreased, indicating that excessive fluoride ions may lead to excessive lattice distortion, which would have an adverse effect on the performance. Fluoride ion doping has little effect on the Curie temperature; the Curie temperature of all samples remained in the range of 176-179℃, indicating that the anion doping modification of this invention can effectively maintain the Curie temperature of lead-free piezoelectric ceramics while significantly improving the piezoelectric performance, demonstrating excellent thermal stability.
[0066] The lead-free piezoelectric ceramics prepared in Examples 1-4 and Comparative Example 1 were subjected to uniform heating at test frequencies of 0.1 kHz, 1 kHz, 10 kHz, 100 kHz, and 1000 kHz, respectively. The relative permittivity values under different temperature conditions were collected in real time, and the relative permittivity-temperature variation curves were plotted. Figures 2 to 6As shown, the lead-free piezoelectric ceramics prepared in Examples 1-4 and Comparative Example 1 exhibit three anomalous peaks between -150 and 200°C, corresponding to three-phase structure changes. With increasing temperature, these represent "trigonal-orthorhombic," "orthorhombic-tetragonal," and "tetragonal-cubic" phase transitions, respectively. It can be seen that the "trigonal-orthorhombic" and "orthorhombic-tetragonal" phase transition peaks are close to and merge with each other, both occurring near room temperature, indicating that the lead-free piezoelectric ceramics of this invention possess a "trigonal-orthorhombic-tetragonal" multiphase structure at room temperature. The third peak appears in the 170-180°C range, indicating that when the temperature rises to this level, the ceramic structure in Examples 1-4 gradually transforms from a tetragonal phase to a cubic phase, resulting in a significant decrease in piezoelectric performance. Of particular note is that, within the "trigonal-orthorhombic-tetragonal" phase transition temperature range, compared to the ceramic in Comparative Example 1, the ceramics in Examples 1-4 exhibit a significant sharpening of the phase transition as the content of Ag2O in the AgF-substituted raw material increases, especially at the "orthorhombic-tetragonal" phase boundary, which is clearly different from the phase boundary dispersion caused by cation doping.
[0067] Therefore, this invention utilizes the above-mentioned anion-doped lead-free piezoelectric ceramics with high voltage performance, as well as their preparation and application, through the use of element A and zirconate Bi. 0.5 (B) 0.5 ZrO3 and AgSbO3 were cationicly modified and sintered to obtain a room-temperature piezoelectric ceramic structure with multiphase coexistence. This structure can refine the ferroelectric domain structure, thereby optimizing the piezoelectric properties. More importantly, based on the multiphase coexistence, AgF was used to replace the original Ag2O as a raw material to achieve the substitution of oxygen ions by fluoride ions, i.e., anion doping. Since different anions have different charges, ionic radii, and electronegativity, their fluoride ion substitution will introduce defects into the crystal lattice, while F... - The high electronegativity of the cation enhances the chemical bond strength between itself and its coordinating cation, inducing stronger local lattice distortion, which in turn affects the phase structure and ultimately results in different piezoelectric properties.
[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. Anion-doped lead-free piezoelectric ceramics with high voltage and high electrical properties, characterized in that: The general chemical formula for lead-free piezoelectric ceramics is: 0.945K. 0.50 Na 0.50 Nb 0.95 A 0.05 O3-0.04Bi 0.5 (B) 0.5 ZrO3-0.015AgSbO 3-x F 2x Where A is Sb, and B includes at least one of Na, K, Li, and Ag; 0 < x ≤0.4, x This represents the molar percentage of AgF replacing Ag2O.
2. The method for preparing anion-doped lead-free piezoelectric ceramics with high voltage performance as described in claim 1, characterized in that: Includes the following steps: S1. According to the molar ratio of the general chemical formula, sodium carbonate, potassium carbonate, niobium pentoxide, antimony trioxide, bismuth trioxide, zirconium dioxide, silver oxide and silver fluoride are used as raw materials. After being ball-milled separately, they are dried and mixed evenly to obtain raw material powder. S2. The raw material powder obtained in S1 is pre-calcined at 700~950℃ for 4~8h. After the heat preservation is completed, it is cooled to room temperature, rolled ball milled again, and dried to obtain the calcined powder. S3. The calcined powder obtained in S2 is granulated, pressed and debinded in sequence to obtain a ceramic body. S4. Sinter the ceramic green body obtained in S3 at 1050~1120℃ for 2~8h to obtain a piezoelectric ceramic body; S5. Silver electrodes are deposited on the surface of the piezoelectric ceramic body obtained in S4, and then it is placed in silicone oil for electric field polarization to obtain lead-free piezoelectric ceramic.
3. The method for preparing anion-doped lead-free piezoelectric ceramics with high voltage electrical properties according to claim 2, characterized in that: In both S1 and S2, the dispersion medium for the rolling ball mill was anhydrous ethanol, and the rolling ball milling time was 4-12 hours.
4. The method for preparing anion-doped lead-free piezoelectric ceramics with high voltage electrical properties according to claim 2, characterized in that: In S3, granulation is carried out by adding a polyvinyl alcohol solution to the calcined powder for granulation. The concentration of the polyvinyl alcohol solution is 6~10wt%.
5. The method for preparing anion-doped lead-free piezoelectric ceramics with high voltage electrical properties according to claim 2, characterized in that: In S3, the pressing process involves using an electric tablet press to compress the granulated powder into tablets. The pressure of the electric tablet press is 8-12 MPa.
6. The method for preparing anion-doped lead-free piezoelectric ceramics with high voltage electrical properties according to claim 2, characterized in that: In S3, the temperature for discharging glue is 750-850℃, and the discharging time is 80-100 minutes.
7. The method for preparing anion-doped lead-free piezoelectric ceramics with high voltage performance according to claim 2, characterized in that: In S5, the temperature of the silicone oil is 25-35℃, the electric field strength for electric field polarization is 2~4kV / mm, and the electric field polarization time is 20~40min.
8. The application of the anion-doped lead-free piezoelectric ceramic with high voltage performance as described in claim 1, characterized in that: It is used in the fabrication of high-sensitivity sensors.